KAJIAN RESIKO PRODUKSI DAN FLUKTUASI HARGA JAGUNG DI KABUPATEN OGAN KOMERING ULU - Lastinawati, Endang (Muhammadiyah University of Palembang, 2016)
This study aimed to analyze the production risks and the risk of fluctuations in the price of corn in the Ogan Komering Ulu (OKU) District. The research area selected intentionally (purposive), with consideration of corn into a commodity in most districts in OKU District. This study uses secondary data (time seriesdata), cover the price of corn in OKU District since January 2010 until December 2014 (60 months) and maize production data in OKU District of the years 2010 to 2014. The results showedthat corn farming likely suffer losses when analyzed in terms of its production, which is indicated by the value of the coefficient of variation of 1,23 or CV> 0,5and a lower limit value of production -5428,62 or L <0. Corn farming is also likely to incur a loss if analyzed from the price fluctuates, indicated by the coefficient of variation in the price of corn of 1,05 or CV> 0,5 so that the lower limit of the price -6531,87 or L <0.